2012
DOI: 10.1038/ijos.2012.33
|View full text |Cite
|
Sign up to set email alerts
|

The role of vascular endothelial growth factor in ossification

Abstract: Osteogenesis and angiogenesis are two closely correlated processes during bone growth, development, remodelling and repair. Vascular endothelial growth factor (VEGF) is an essential mediator during the process of angiogenesis. Based on an extensive literature search, which was carried out using the PubMed database and the keywords of osteogenesis, VEGF, endochondral ossification and intramembranous ossification, this manuscript reviews the role of VEGF in ossification, with emphasis on its effect in endochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
184
3
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(193 citation statements)
references
References 51 publications
(66 reference statements)
2
184
3
4
Order By: Relevance
“…Endothelial cell growth is regulated by vascular endothelial growth factor (VEGF), which also acts as an essential mediator during endochondrial ossification and intramembranous ossification. VEGF is involved in many processes, including osteoblast differentiation and recruitment of osteoclasts, and previous evidence suggests joint contribution of angiogenesis and bone formation during skeletal development 34, 35…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell growth is regulated by vascular endothelial growth factor (VEGF), which also acts as an essential mediator during endochondrial ossification and intramembranous ossification. VEGF is involved in many processes, including osteoblast differentiation and recruitment of osteoclasts, and previous evidence suggests joint contribution of angiogenesis and bone formation during skeletal development 34, 35…”
Section: Discussionmentioning
confidence: 99%
“…In vitro analysis from donor 1 showed a decrease in both VEGF and COLX gene expression compared to the other two donors. VEGF is known to be involved in vascularisation (Yang et al, 2012), which means that this decreased expression of VEGF could be attributed to the lack of bone marrow elements we observed following in vivo implantation. Additionally, donor 1 showed greater COLII expression and GAG accumulation, as well as, decreased COLX gene expression compared to donors 2 and 3.…”
Section: Ca Knuth Et Almentioning
confidence: 96%
“…26 Based on these data it could be concluded that the small-sized bone substitute granules might also induce a higher or faster level of bone tissue growth, as VEGF also stimulates the proliferation and differentiation of osteoblasts in a dose-dependent manner. 51,52 However, further studies have to be conducted using also bone implantation models to clarify this issue.…”
mentioning
confidence: 99%